Pengaruh Kekasaran Permukaan Terhadap Sambungan Hasil Las Titik Pada Material Baja Karbon Rendah - Yanto, Febri, Muh. Alfatih Hendrawan ST., MT, Ir. Agus Hariyanto, M.T (2015)
Spot welding (spot welding) is the way in which the welding surface pressure plate connected with a large electrified through metal electrodes that intersect. In use the welding parameters greatly affect the outcome of the welding. The purpose of this study was to determine the effect of surface roughness on the physical and mechanical properties at the weld joint point. The material used in this study is the low carbon steel with a thickness of 0.8 mm. Current variation used is 3000 A, 4000 A and 5000 A with the welding time for 0.3 sec; 0.4 dt; and 0.5 dt. While the variation of surface roughness used are original surface, the surface sandpaper, and sandblasting. Tests of chemical composition using a spectrometer with ASTM E 415. The mechanical properties of welded joints results can be analyzed using shear testing (Tensile Shear Load Bearing Capacity) using a Universal Testing Machine (UTM) with standard AWS D8.9-97. The physical properties of the weld joint can be analyzed using a macro photo SZX7 Olympus microscope brands and micro photo using the brand Olympus microscope with ASTM E407-07. The test results show the chemical composition of carbon steel plate falls into the category of low carbon steel with the type of hypo-eutectoid. The test results showed that the variation of the current slide, time, and a significant effect of surface roughness. The observation of macro photographs show that the larger the width of the weld metal with increased flow, time, and different surface roughness. While the test results of the parent metal micro photo low carbon steel has a ferrite and pearlite phase. In the test results of micro photo HAZ area remains that of ferrite and pearlite, but the size is more subtle than the parent metal. While the weld metal phase is formed martensite. Keywords: welding point, low carbon steel, chemical composition, shear test, metallographic